PECULIARITIES OF STRUCTURAL AND MORPHOMETRIC REORGANIZATION OF THE LUNGS VESSELS AFTER EXPERIMENTAL THERMAL TRAUMA - Небесна, З.М.; Волков, К.С.; Литвинюк, С.О. (World of Medicine and Biology, 2015)
In the experiment on mature white male rats histological and morphometric research of the lungs were made after thermal injury. It was established that the degree of structural and morphometric vascular changes in components of organ depends on the term of experiment. In the early stages after burn injury (1-7 days of experiment ) by adaptative-compensatory changes and initial signs of destructive of vascular in components of organ were revealed. In the later stages (14-21 days of experiment) significant destructive-degenerative vascular disorders were found.
Keywords: pulmonary vessels; histologic and morphometric changes; thermal trauma